A study on factors contribute to student’s anti-social behaviour at Maktab Rendah Sains Mara, Batu Pahat, Johor / Intan Raihana Redzuan and Nur Liyana Zainal - Redzuan, Intan Raihana; Zainal, Nur Liyana (Faculty of Administrative Science and Policy Studies, 2014)
Anti-social behavior is the behavior that is deemed strange, or contradictory to local norms and values. Student anti-social behavior can be defined as the deviant behavior that contradicts to the norm and values as a student. The study examines the factors that contribute to the anti-social behavior among students at Maktab Rendah Sains Mara Batu Pahat, Johor. In this study, 160 of questionnaire were distributed to the student respondents at MRSM Batu Pahat Johor. According to the findings, it was recognizing the media influence had become the most influential factor that contributes to student’s anti social behaviour at MRSM Batu Pahat Johor. Parenting style and peer pressure also have significant relationship to the student anti-social behavior. From researcher’s case study, the researchers can see that there are a number of students who commit anti social behaviour without they realize it. Every entities must step forward to overcome this problem must be instantaneously implement in order to control the problems. It is not the mistake by the individual themselves, but it concern all in the society.